ArtISCoG artificial immune system for coloring graphs - Cebreros, Julius Aniceto D.; Dulfo, Lemuel D. (2008)
The graph coloring problem (GCP) is an example of an NP-Complete Problem with numerous practical real world applications. Most heuristic, meta-heuristic and genetic algorithms have already been tried in solving this problem. This study proposes using an immune inspired algorithm, CLONALG in handling the GCP. In this approach, the graph is treated as an antigen and its corresponding solutions as the antibodies. Using a fitness function, the best fit antibody becomes the optimized solution. Experiment results show that an immune inspired algorithm is a feasible approach in solving the graph coloring problem.